On the semantics of possessive pronouns in Ukrainian - Olesia Sulyma (Енциклопедичний Вісник України)
This article deals with the complexities of possessive pronouns in the Ukrainian language, with a particular emphasis on their practical application in editing, especially for encyclopedia entries. The author conducts a thorough analysis of the semantic and syntactic features of these pronouns, revealing how their meanings can extend beyond the traditional notion of ownership to encompass a wider range of semantic nuances, such as characteristics, properties, and relationships. By examining a variety of linguistic contexts, the study illuminates the versatility of possessive pronouns in Ukrainian and provides valuable insights for editors and language learners alike.